Leaf Functional Traits of Invasive Grasses Conferring High-Cadmium Adaptation Over Natives - Ilyas, Muhammad; Shah, Sakhawat; Lai, Ya-Wen; Sher, Jan; Bai, Tao; Zaman, Fawad; Bibi, Farkhanda; Koul, Monika; Wani, Shabir Hussain; Majrashi, Ali; Alharby, Hesham F.; Hakeem, Khalid Rehman; et al. (Frontiers in Plant Science, 2022)
Heavy metal (HM) contamination resulting from industrialization and urbanization during the Anthropocene epoch, and plant invasion can severely threaten the growth and adaptation of local floras. Invasive alien plant species generally exhibit a growth pattern consistent with their functional traits in non-contaminated environments in the introduced range. However, it remains unclear whether invasive alien plants have an advantage over native plants in contaminated environments and whether this growth pattern is leaf functional traits dependent. Here, we selected two congeneric pairs of invasive alien and native grasses that naturally co-exist in China. To evaluate the effect of cadmium (Cd) on the structural and physiological leaf traits, we grew all four species in soil contaminated with or with 80 mg/kg Cd. Invasive plants contained significantly higher concentrations of Cd in all three organs (leaf, stem, and root). They displayed a higher transfer factor and bioconcentration factor (BCF) of shoot and root than natives, indicating that invasive species are potential Cd hyperaccumulators. Invasive plants accumulated polyphenol oxidase (PPO) to higher levels than natives and showed similar patterns of leaf structural and physiological traits in response to changes in Cd bioconcentration. The quantifiable leaf structural traits of invasive plants were significantly greater (except for stomatal density and number of dead leaves) than native plants. Leaf physiological traits, chlorophyll content, and flavonoid content were also significantly higher in invasive plants than in natives under Cd stress conditions after 4 weeks, except for nitrogen balance index (NBI). Chlorophyll fluorescence parameters decreased, except for the quantum yield of photosystem II (ΦPSII) and the proportion of open photosystem II (qP), which increased under Cd stress conditions in both species. High-Cd adaptation of invasive grasses over natives suggests that invasive plants possess optimal leaf structural and physiological traits, which enable them to adapt to stressful conditions and capture resources more quickly than natives. This study further emphasizes the potential application of invasive alien plants in contaminated soil environments within the introduced range. To a certain extent, some non-invasive alien plants might adapt to metalliferous environments and serve as hyperaccumulator candidates in phytoremediation projects in contaminated environments.